IMPLEMENTASI PEMBELAJARAN PROYEK BERBASIS ECOPRINT DALAM MENINGKATKAN KREATIVITAS PESERTA DIDIK FASE F DI SMA AL- ISTIQAMAH PASAMAN BARAT - Widiyawati; Slamet Rianto; Loli Setriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the lack of creativity among students in project-based ecoprint learning at SMA AL-ISTIQAMAH Pasaman Barat. This study uses a qualitative method with purposive sampling as the data collection technique, involving observation, interviews, and documentation. The researcher used N-vivo 15pro analysis techniques such as data import, data coding, project visualization, and extract reports. The results obtained from the research indicate that the ecoprint-based project successfully increased creativity, promoted student-centered learning, encouraged collaboration, and allowed students to express creative ideas during the project-based ecoprint learning. Similarly, the results from the interview diagram with administrative staff, the ecoprint coordinator, and educators show that the implementation of project-based ecoprint learning in enhancing student creativity at SMA AL-ISTIQAMAH Pasaman Barat is effective and can improve student creativity.